Workshop Pemanfaatan Platform Gatherich Dalam Meningkatkan Literasi Keuangan Mahasiswa Pendidikan Ekonomi - Lenlioni, Liling; Alexandro, Rinto; Rahman; Hidayati; Rakhmawati, Dewi; Buji, Grace Evelina; Puspita, Dwi Della; Setyanto, Zola Ari; Agustin, Yul (Jurnal Pengabdian Kampus, 2023)
The community service activity was carried out on April 10, 2023 in the classrooms of the economics education study program, the Teaching and Education Faculty, Palangka Raya University, the participants who took part in this activity were 34 undergraduate students of the Economics Education Study Program,  the Teaching and Education Faculty, Palangka Raya University. The community service activities carried out aim to increase financial literacy in students regarding the use of the Gatherich platform. This community service activity was carried out in the environment in  economic education study program students. The results of this community service activity show that students of the Economics Education Study Program are enthusiastic about increasing their financial literacy. This is reflected in the participation of students in activities and being active in discussion sessions during the activities